The Study of Water Media in Green Towerâ€™s Solar Collector - Hailmee Solihin, Zainoor; Wisnoe, Wirachman; Zailani, Ramlan; Yusoff, Noriah (International Journal of Engineering and Technology, 2018)
In general, the solar collector of a Green Tower is either air-filled or empty space. This condition allows the solar chimney to have constant air flow supply from the solar collector. In this study, water media is introduced inside the solar collector as an effort to increase the performance of the Green Tower. As solar energy is harvested, energy is stored inside the collector. Thus, this study investigates the Green Tower performance using the solar collector with water-filled media. Â The investigation is done by simulating the solar collector with water-filled condition using Computer Fluid and Dynamic (CFD) software. From here, the viability of employing the water-filled solar collector is validated. This report presents the mathematical model of the understudied conditions and compared against the experimental as well as simulation data. The simulation results show that the Green Tower's performance is very promising with good temperature output were recorded at 55Â°C and temperature difference between CFD2 (water medium) and CFD1 (air medium) was steadily recorded at approximately 12Â°C. Increased in the resulting temperature is observed by using the water-filled solar collector.Â However, the air velocity is recorded near identical between CFD1 and CFD2 due to thermal coefficient of water is higher compared to air thus resist the heat to be transferred into the heat exchanger. In conclusion, the temperature distribution inside the Green Tower is increased because of using water as a medium inside the solar collector.Â But, the heat stored inside the collector remains longer with water-filled medium thus, this condition allows the Green Tower to function during the night time as well; when the solar radiation is unavailable.Â Â